Redefining Literacy: Nigeria in Perspective - Zua, Biale (Advances in Social Sciences Research Journal, 2022)
Literacy is a term that has developed a new meaning in the 21st century. Traditionally, literacy is understood as the ability to read, write, and calculate or do arithmetic. However, most recently, with the advent of technology and digital media, the global definition of literacy has been expanded to include visual expressions and a lot more. In these ever-changing phases of globalization, literacy extends to skills and tools that enable an individual to function in society. The acquisition of these tools and skills is mandatory for any individual to be considered literate. Specific institutions and organizations are responsible for providing the learning spaces and environments, whether private or public. Learners at various levels of education should acquire the tools and skills required for that level. Therefore, it is crucial for the institutions and organizations responsible for providing these tools and new materials to be well-equipped and to have qualified teachers. The administration must provide transformational literacy instruction to meet the challenges of the individual learners to function globally.